2006
DOI: 10.1097/01.mao.0000180484.24242.54
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Biology of Vestibular Schwannomas: Dissecting the Pathogenic Process at the Molecular Level

Abstract: Great strides have been made to identify why vestibular schwannomas develop at the molecular level. Continued research is needed to find targeted therapies with which to treat these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 104 publications
1
50
0
Order By: Relevance
“…Since 1997, when the most recent set of diagnostic criteria were proposed, the natural history of NF2 has become more clearly defined, 19 -24 and management of the disease has improved. 1,2,25-27 Molecular testing for NF2 mutations has become clinically available, 1,2,26,28,29 and somatic mosaicism has been found to occur in 25-30% of de novo NF2 patients. 11,12 Schwannomatosis has been defined as a distinct clinical entity, 9 excluded from the NF2 locus, 30 and shown to be related to mutations of the SMARCB1 locus in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1997, when the most recent set of diagnostic criteria were proposed, the natural history of NF2 has become more clearly defined, 19 -24 and management of the disease has improved. 1,2,25-27 Molecular testing for NF2 mutations has become clinically available, 1,2,26,28,29 and somatic mosaicism has been found to occur in 25-30% of de novo NF2 patients. 11,12 Schwannomatosis has been defined as a distinct clinical entity, 9 excluded from the NF2 locus, 30 and shown to be related to mutations of the SMARCB1 locus in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Given the heterogeneity of the clinical response to various types of mutations, no clear genotype/phenotype correlation has been established [9]. However, a recent study reported a significant relationship between tumor behavior and genetic alteration in Chinese patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…50,51 In vitro, treatment of NF2-deficient cells with HER-1/EGFR inhibitors can reduce cellular proliferation. The finding that overexpression of various growth factor receptors in sporadic VS correlate with higher growth rate 26 further spurred efforts to find drug therapies that could be used as molecular targeting agents for these tumors.…”
Section: Current Experience With Targeted Chemotherapymentioning
confidence: 99%